TINJAUAN YURIDIS DARI AKTA OTENTIK YANG DIBUAT OLEH NOTARIS YANG DALAM MASA PENAHANAN - Duarta, Ni Wayan Yunika; Sutrisni, Ni Komang (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Notary is a public official who is authorized to make authentic deeds, as stated in Article 1868 BW that stated in Article 1868 BW. Law of the Republic of Indonesia Number 2 Year 2014 concerning the amendment to Law Number 30 of 2004 concerning the Office of Notary, specifically Article 9 paragraph (1) letter e states that the Notary is temporarily dismissed from his/her position because of the from his/her position because she/he is in detention. Meanwhile, in Article 9 paragraph 2, the Notary is given the opportunity to defend himself before the Supervisory Panel in stages, temporary dismissal of Notary as referred to in paragraph (2) is carried out by the Minister on the proposal of the Central Supervisory Council (Article 9 paragraph (3)). The meaning of the statement in Article 9 paragraphs (2) and (3) of the Notary Public Office Act contains several interpretations that the temporary dismissal will be carried out if the Supervisory Council has proposed to the minister, and during the period of self-defense and decision from the minister, the notary can still exercise his authority in accordance with Article 15 of the Law of Notary Position. This research uses normative legal studies. The conclusion can be drawn the authority of a notary who is in detention in exercising his authority to make an authentic deed is authorized if the Minister's decree on temporary dismissal has not been issued and is not authorized after the issuance of the Minister's decree on temporary dismissal. The legal effect of the deed is the authentic deed still has perfect evidentiary power if the ministerial decree on temporary dismissal has not been issued and it is not relegated to a deed under the hand.